The response of the tropical forest stand to silviculture operations - Favrichon, V.; Dupuy, B.; Maitre, H.F.; Nguyen-The, N.; Damio, T.; Doumbia, N.; Kadir K.; Petrucci, Y.; Sist, P. (1997)
The CIRAD-Forest Research Programme on the dynamics of humid tropical forests has been in operation since 1974 in collaboration with various national forest research institutes. Research is carried out on a network of experimental plots, of which the most important are in Africa (Mopri, Irobo and La Téné in Côte d’Ivoire and M’baiki in the Central African Republic), South America (ZF2 at Manaus in Brazil and Paracou in French Guiana) and Asia (Strek at Berau in Indonesia). These plots have been designed with a common methodology and are followed up consistently. They enable study of the dynamics of humid tropical forest ecosystems and the response of different types of forest to disturbances such as commercial logging and therapeutic thinning. Much research has been carried out on these plots. Some of the results obtained have already led to the implementation of large-scale forest management projects based on the principles of sustainable management (Yapo in Côte d’Ivore, for example). The aim of this article is to present an overview of these plots and to outline the main response trends of the forest stand to sylviculture interventions. In the first part, the parameters of the average natural forest are given (in terms of growth rate, expansion and mortality). By showing how these parameters change over time after sylviculture interventions, the effect of stand density on productivity and the influence of harvesting and thinning on the recovery rate of the forest stand can be assessed.